Immobilizing Bacillus subtilis on the carrier of poly (acrylic acid)/sodium bentonite for treating sludge from Pangasius fish ponds - Nguyen, Thanh Duoc; Doan, Binh; Pham Thi , Thu Hong (Nuclear Science and Technology, 2016)
Sodium bentonite (NaBent) was modified by poly(acrylic acid) (PAAc) to prepare the carriers for immobilization of Bacillus subtilis. Different mixtures of NaBent/AAc were regularly dispersed in distilled water and irradiated under gamma rays at an absorbed dose of 6.5 kGy with dose rate of 0.85 kGy/hr in air for polymerization of acrylic acid and formation of poly(acrylic acid)/sodium bentonite (PAAc–NaBent). The reaction yield was determined with the initial concentration of acrylic acid (AAc). The functional group properties of the resulting PAAc–NaBent were analyzed by Fourier Transform Infrared spectra (FTIR). Bacillus subtilis cells were immobilized on both NaBent and PAAc–NaBent as carriers by adsorption method for treating the sludge contaminated by fish feces and residual feed from the Pangasius farming ponds. The results showed that immobilization capacity of Bacillus subtilis on the PAAc–NaBent was better than that on non-modified NaBent. Analysis of BOD for the farming pond water containing Bacillus subtilis and the bacteria immobilized carriers with time revealed the lower BOD values obtained with the samples containing PAAc–NaBent, suggested that degradation of organic pollutants by Bacillus subtilis immobilized on the PAAc–NaBent was faster than that by free bacteria.